Encouraging Trust In Social Media And Social Commerce Intention: Do Informational Support And Emotional Support Matter? - Burhanudin Burhanudin; Riswandha Ramadhani; Rhea Ledesma-Gumasing (Jurnal Manajemen Indonesia, 2023)
Social media has transformed into social commerce; therefore, a greater understanding of social commerce is crucial. As a social media site, TikTok earns more profit through its social commerce, TikTok Shop. This study examines the influence of informational and emotional support on trust in social media and social commerce intention. A survey was conducted among 242 TikTok Shop users, and the data was analyzed using structural equation modeling. In this study, it is revealed that informational support affects trust in social media significantly but that informational support does not influence social commerce intention. Moreover, both trust in social media and social commerce purposes were influenced considerably by emotional support. Finally, trust in social media mediates the relationship between informational support and s and between emotional support and social commerce intention. Keywords: Informational support; Emotional support; Trust in social media; Social commerce intention.